Peran Konseling Kelompok Terhadap Konformitas Teman Sebaya Pada Remaja - Wahyu Auliazalsini; Makhriffah Robbiah Addawiyah; Siti Habibah; Adibah Nur Damiyati; Aura Islamyazizah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
A scientific paper that reviews the literature on the role of group counseling on young people's peer conformity attempts to develop a novel intervariable influence study hypothesis that will be used to future psychology counseling studies. This literature review was written using a library research approach, using internet resources from academic websites like Mendeley, Google Scholar, and others consulted. The article literature review has found a number of group counseling techniques for reducing the conformity of peer therapy ata young age, among them are custom-emotive behavior therapy, self instruction techniques, assertive training techniques, homeroom techniques, and self management techniques.